Um reino de muitos reinos: a busca de uma causa ausente em Gonçalo Tavares - Simioni, Ronan (2017)
Our study arises from the imperative need to understand the current historical moment that we live. The the second decade of the twenty-first century early years have shown the reappearance of movements that we supposed to be only in the documents that record our past times. However, this period has revealed that the global territorial disposition still presents itself as unfinished and that the rise of fundamentalist movements (in both political and religious spheres) has not disappeared from our reality. In an attempt to answer our questions, we have chosen the literary text, considering its privileged place occupied in relation to the capture of the real, as a way of access to the understanding of the world sought here. Thus, is the tetralogy O Reino of the Angolan writer residing in Portugal Gonçalo M. Tavares, that serves as analysis object in the present paper. In these four narratives, is possible to visualize the representation of various events alluding to facts recorded throughout history. So, we divided our analysis of the works into three different moments. Initially, we are concerned with demarcating this referentiality from the first two novels of the series: Um Homem: Klaus Klump and A Máquina de Joseph Walser, in which the imperialist impulse and the use of violence make up the tonic of actions. Jerusalém, the third of the four texts brings with it the representation of individuals strongly traumatized by events similar to those seen in previous times, beings reduced to the lowest human life common denominator. In the sequence, Aprender a Rezar na era da Técnica emerges as the formulation of a new government clearly with totalitarian inclinations, element that in addition to demarcating certain cyclical involving the four narratives, portrays the strong connection between them allowing this division in three interconnected moments. Finally, we discuss the idea of Absent Cause, our main analytical postulate used in order to better understand the tavarian narratives, relating it to the current possibilities of Historical Novel.